Upaya Peningkatan Aktivitas dan Hasil Belajar Siswa Pada Pembelajaran Fisika Menggunakan Model Pembelajaran Kooperatif Teknik Two Stay Two Stray di SMA - Mulyati, Mulyati; Putri, Fhadira Insani; Deswalman, Deswalman (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: The research aims to increase students' activity and learning outcomes in Class X in Senior high school 10 Kota Jambi. Methodology: The research method used is mixed. This research is a Classroom Action Research carried out in three cycles. Retrieval of qualitative data using student activity observation sheets and teacher activity during the teaching and learning process. Retrieval of quantitative data in the form of objective tests held at the end of each learning cycle. Main findings: From the results of the study, it showed that there was an increase in learning outcomes for each cycle, namely, 59.53 for the cycle I to 69.38 for cycle II and 75.48 for cycle III. While increasing the average percentage of student activity. In cycle I was 47.24%, the average percentage of student activity increased to 60.17% in cycle II, and experienced another increase in cycle III to 70.87%. Novelty/Originality of this study: That research using the two stay two stray learning model to improve learning outcomes is very little done in high schools, mostly the application of the two stay two stray model is applied in elementary schools